Discussion of the Predictive Power of First-Quarter Earnings Reports: A Replication - Holton, Thomas L. (Journal of Accounting Research, 1966)
It may be that my only significant comment will be, don't believe have heard that figures do not lie, but liars do figure; I think that, in this case, the figures do perhaps lie. One thing I cannot resist saying a little about is this matter of so much emphasis on earnings per share. I am almost unwilling to participate in the discussion on this subject that gives so much emphasis to it. Of course, theoretically, that is only one factor that is used in evaluating common stocks. But I am afraid it is the only factor in too many instances. Now I hear that the Accounting Principles Board of the AICPA is going along with the trend and has plans to require earnings per share at the bottom of all earnings statements. Early in the paper, the authors state, We suppose the purpose of interim reports is to assist the interested outsider in foretelling the contents of the coming annual report. 1 Well, I think that is just one purpose. Interim reports, as well as annual reports, serve as a report on stewardship and accountability as a factor in judging management. I recognize, however, that one very important factor in all accounting information of a historical nature is to give a clue as to what can be expected in the future Obviously, there is no reason for studying history at all, except that it might help one make decisions as far as the future is concerned. But interim earnings per share can be overemphasized or used without appropriate discretion. In another statement, apparently intending to be critical, the authors state that interim reports are prepared by approximately the same techniques as annual reports. Well, why not? I think we could easily get a